1991
DOI: 10.1148/radiology.180.2.2068324
|View full text |Cite
|
Sign up to set email alerts
|

Osteomyelitis: characteristics and pitfalls of diagnosis with MR imaging.

Abstract: Prospective and retrospective magnetic resonance (MR) imaging (0.35-T) interpretations were compared with final diagnoses in 110 patients suspected to have osteomyelitis. Diagnostic criteria of dark marrow on T1-weighted images and bright marrow on short-tau inversion-recovery images yielded a prospective sensitivity of 98% and a prospective specificity of 75%. Sixty percent of uncomplicated septic joint effusions demonstrated abnormal marrow signal intensity that was mistaken for osteomyelitis. Retrospective … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
91
2
10

Year Published

1993
1993
2015
2015

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 242 publications
(107 citation statements)
references
References 0 publications
4
91
2
10
Order By: Relevance
“…The combination of these images increases specificity from 75 to 82%. 19 The sensitivity is 100%. The CT is particularly useful in the evaluation of intramedullary osteitis.…”
Section: Mri and Ctmentioning
confidence: 99%
“…The combination of these images increases specificity from 75 to 82%. 19 The sensitivity is 100%. The CT is particularly useful in the evaluation of intramedullary osteitis.…”
Section: Mri and Ctmentioning
confidence: 99%
“…The MRI findings in SBO are classical. Highly sensitive but non-specific MR findings of osteomyelitis include marrow T1 hypointensity and T2 hyperintensity [9]. Chang et al reported clival marrow and preclival soft tissue abnormalities in all their cases [1].…”
Section: Discussionmentioning
confidence: 99%
“…MRI has high sensitivity and specificity for the diagnosis of both osteomyelitis and soft tissue infections [7,11]. MRI accurately depicts edematous, diseased bone and differentiates diseased bone from normal bone.…”
Section: Discussionmentioning
confidence: 99%
“…Magnetic resonance imaging (MRI) has high sensitivity for the diagnosis of musculoskeletal infection and also delineates with detail the extent of the osseous and soft tissue involvement [7,11,15,17]. Studies on pediatric pelvic osteomyelitis using MRI demonstrate adjacent muscle abscesses in 20% to 55% of patients [4,5,14,15,17].…”
Section: Introductionmentioning
confidence: 99%